Antidepressant-like Effects of Cannabis sativa L. Extract in an Lipopolysaccharide Model: Modulation of Mast Cell Activation in Deep Cervical Lymph Nodes and Dura Mater - Joonyoung Shin; Dong-Uk Kim; Gi-Sang Bae; Ji-Ye Han; Do-Won Lim; Young-Mi Lee; Eunjae Kim; Eunjeong Kwon; Dongwoon Han; Sungchul Kim (MDPI AG, 2024)
Background: Lipopolysaccharide (LPS)-induced neuroinflammation is a well-established model for studying depression-like behavior, driven by pro-inflammatory cytokines such as TNF-α and IL-1β. Mast cells (MCs) contribute to neuroinflammation by releasing mediators that exacerbate depressive-like symptoms. This study evaluates the antidepressant-like and anti-inflammatory effects of Cannabis sativa L. inflorescence extract (CSL) in an LPS-induced neuroinflammation model. Methods: Male C57BL/6 mice were intraperitoneally injected with CSL at doses of 10, 20, and 30 mg/kg, 30 min prior to LPS (0.83 mg/kg) administration. Depressive behaviors were assessed using the sucrose preference test (SPT), tail suspension test (TST), and forced swimming test (FST). The neutrophil-to-lymphocyte ratio (NLR) was measured to assess systemic inflammation. Cytokine levels in the prefrontal cortex (PFC) were measured, and mast cell degranulation in the lymph nodes and dura mater was analyzed histologically (approval number: WKU24-64). Results: CSL significantly improved depressive-like behaviors and decreased the NLR, indicating reduced systemic inflammation. CSL also significantly reduced TNF-α and IL-1β levels in the PFC. Furthermore, CSL inhibited MC degranulation in the deep cervical lymph nodes and dura mater, with the strongest effects observed at 30 mg/kg. Conclusions: CSL demonstrated antidepressant-like and anti-inflammatory effects in an LPS-induced neuroinflammation model, likely through the modulation of cytokine expression and mast cell activity. These results suggest the potential of CSL as a therapeutic option for treating inflammation-related depression.